TECHNIQUE FOR DETERMINING AVERAGE PLANE OF PIPE TAPS BY A TRIANGULATION METHOD USING AN ANTROPOMORPHIC ROBOT - N. S. Lyubimyi; B. S. Chetverikov; M. S. Chepchurov; I. A. Odobesko (Вестник СибАДИ)
Introduction. Nowadays there are various manufacture methods of pipe taps. One of the most laborious operations during manufacture is a marking of pipe taps for subsequent machining. Work layout operations are performed using special tool ware and outfit. These operations are performed manually and it leads to the decrease in accuracy and to the increase of laboriousness. The authors suggest the method of determination of the latent base of pipe tap (average plane) using an anthropomorphic robot. The results of research would help to make the virtual calculation of tool position of the anthropomorphic robot for marking and to generate the robot trajectory. Ultimately, such research would also decrease laboriousness and increase accuracy of marking operation.Materials and methods. The authors suppose to use latent base, namely the average plane of the pipe tap as a measuring base. The robot is calibrated from the base plane placement and chooses the shortest circular arc by comparative approach. Therefore, such shortest arc would form the average plane. The authors carry out the determination of the curve line length by the triangulation method using the interferometer.Results. The result of the research is the technology development for determination of latent base in the average plane form.Discussion and conclusions. The proposed method of latent bases determination of pipe tap would allow making the automated system of marking of pipe taps. Moreover, such method would help to reduce time of performing operations as well as to decrease the manufacture laboriousness on the following stage of technological process.